2008
DOI: 10.1007/s10886-008-9537-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in Plant Defense Alters Effects of Root Herbivores on Leaf Chemistry and Aboveground Herbivore Damage

Abstract: Root herbivores can indirectly affect aboveground herbivores by altering the food quality of the plant. However, it is largely unknown whether plant genotypes differ in their response to root herbivores, leading to variable defensive phenotypes. In this study, we investigated whether rootfeeding insect larvae (Agriotes sp. larvae, wireworms) induce different responses in Plantago lanceolata plants from lines selected for low and high levels of iridoid glycosides (IG). In the absence of wireworms, plants of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
2
48
2
Order By: Relevance
“…Interestingly, on ribwort plantain, Plantago lanceolata that were exposed to belowground herbivory by Agriotes spp., aboveground herbivory levels were three times lower on a high-iridoid glycoside (secondary defense metabolites in Plantago) producing lineage, compared to controls without root herbivores. In contrast, herbivory levels were nine times higher in response to the root herbivore on a low iridoid glycoside lineage (Wurst et al, 2008). This study illustrates that the genetic background of a plant can play an important role in determining plant-mediated effects of root insect herbivores on aboveground chewing insect herbivores.…”
Section: The Effect Of Root Herbivores On Aboveground Herbivoresmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, on ribwort plantain, Plantago lanceolata that were exposed to belowground herbivory by Agriotes spp., aboveground herbivory levels were three times lower on a high-iridoid glycoside (secondary defense metabolites in Plantago) producing lineage, compared to controls without root herbivores. In contrast, herbivory levels were nine times higher in response to the root herbivore on a low iridoid glycoside lineage (Wurst et al, 2008). This study illustrates that the genetic background of a plant can play an important role in determining plant-mediated effects of root insect herbivores on aboveground chewing insect herbivores.…”
Section: The Effect Of Root Herbivores On Aboveground Herbivoresmentioning
confidence: 74%
“…In field studies, plant-mediated effects of coleopteran root herbivores on aboveground chewing herbivores can be neutral (Hunt-Joshi et al, 2004;Barber et al, 2015;Borgström et al, 2017), positive (Wurst et al, 2008), or negative (White and Andow, 2006;Wurst et al, 2008;Megías and Müller, 2010, see Figure 2D, Supplementary Table 4). Interestingly, on ribwort plantain, Plantago lanceolata that were exposed to belowground herbivory by Agriotes spp., aboveground herbivory levels were three times lower on a high-iridoid glycoside (secondary defense metabolites in Plantago) producing lineage, compared to controls without root herbivores.…”
Section: The Effect Of Root Herbivores On Aboveground Herbivoresmentioning
confidence: 99%
See 1 more Smart Citation
“…differences in the production of toxic compounds that affect soil organisms. However, belowground effects of intraspecific plant variation on plant-animal interactions have only been studied to a limited extent and mostly within single organism groups (Andersen et al 2007;Griffiths et al 2005;Wardle 2006;Wurst et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the concentrations of these compounds in shoots and roots can have strongly negative effects on the performance of generalist above-and belowground insect herbivores, but that they can be used as feeding cues and oviposition stimulants by specialist insect herbivores (e.g. Bowers and Puttick 1989;Nieminen et al 2003;Wurst et al 2008;Reudler Talsma et al 2008, 2011.…”
Section: Introductionmentioning
confidence: 99%